Losses caused by Groundnut ringspot tospovirus in peanut crop in the State of São Paulo - Michelotto, Marcos Doniseti; Carrega, Willians César [UNESP]; Prado Lamana, Luis Eduardo; De Souza, Tamiris Marion; De Godoy, Ignácio José; De Nazaré Almeida Dos Reis, Luciane; Menezes Sales, André Luis; De Cássia Pereira Carvalho, Rita (Universidade Estadual de Londrina, 2019)
An increased incidence and severity of Orthotospovirus species has been observed in the peanut crop. The typical symptoms of the virus, usually known as ringspot in peanut and spotted wilt in other crops, include mosaic, chlorotic ring-shaped spots, necrosis, and plant stunting. This study aimed to verify the occurrence of this virus in peanut growing areas in the São Paulo State, Brazil, identify the predominant virus species, and determine losses resulting from the presence of this virus. Surveys were carried out in four peanut commercial areas sown in the municipalities of Santa Adélia and Cândido Rodrigues in the 2014/2015 season using the cultivar Granoleico. The following parameters were evaluated: plant stand, number of plants with symptoms, and severity of these symptoms through a scoring scale of visual symptoms. The results showed that the predominant virus species is Groundnut ringspot tospovirus (GRSV). Also, the lower the stand is, the higher the percentage of plants with virus symptoms. The mean incidence of GRSV in commercial peanut areas is 40%, with mean losses estimated at 38% when GRSV is present and 64% when there is the presence of virus and reduction in plant density.
Keywords: Arachis hypogaea L; Incidence; Severity; Tospovirus; Yield